Climate risk and the Norwegian exchange rate - Qaisar Farooq Akram (Norges Bank, 2024)
This study discusses whether climate risk, in the form of physical risk and transition risk, may cause an appreciation or depreciation of the Norwegian krone. Exchange rates reflect relative prices between money, goods, and services of different countries. Since countries vary greatly in their exposure to and capacity to manage different types of climate risk, assessing the exchangerate impact of climate risk entails evaluating how much a country may lose or gain from climate risk compared to its trading partners. The study highlights several factors suggesting that the Norwegian krone may face lower climate risk over time compared to the currencies of trading partners. It also investigates empirically whether climate risk has affected the krone exchange rate over the past decade. The results suggest that climate risk has not contributed to fluctuations in the krone exchange rate over the examined period.
hdl:11250/3170177
Keywords: Q54; Q56; Q58; F31; F37; 330; Climate risk; stranded assets; exchange rates; green transition